Synthesis of nanocomposites of PMN-PT-BT with metal oxides via surface modification - Han, Kyoung R.; Park, Soyoung; Kwon, Young-Soon; Kim, Chang Sam (SPRINGER, 2006)
Low-temperature-sinterable PMN-PT-BT [0.96 (0.91Pb(Mg1/3Nb2/3)O-3-0.09PbTiO(3))-0.04BaTiO(3)] powder was first prepared by the modified mixed oxide method and then metal (M=Cu, Mg, Ag) oxides were introduced as their nitrate salts. Precalcined PMN-PT-BT/MO composite powders were surface modified with the magnesia sol to suppress diffusion of Ag or metal oxides. Such prepared composite powders were sintered > 98% T.D. at 850 - 900 degrees C and showed homogeneous microstructures with < 100 nm Ag or metal oxide particles. Nanoparticles were located mostly in grains and some on grain boundaries. Grain growth was substantially inhibited and resulted in grain size of similar to 2 mu m. The nanocomposites of PBT/Ag and PBT/MgO showed substantially improved sintered densities and dielectric properties at sintering temperature below 1000 degrees C, but the PBT/CuO composite was hardly affected. The PBT/ Ag composites treated with the MgO sol showed good handling strength of MOR > 120 MPa. The proper amount of the magnesia sol for surface modification seemed to be 0.5-1.0 wt.
Keywords: PIEZOELECTRIC PROPERTIES; DIELECTRIC-PROPERTIES; CERAMICS; TEMPERATURE; 0.9PB(MG1/3NB2/3)O-3-0.1PBTIO(3); FABRICATION; COMPOSITES; SILVER